2015
DOI: 10.1016/j.jvoice.2014.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Dysphonia in Nursing Home and Assisted Living Residents: Prevalence and Association With Frailty

Abstract: Objective Previous studies of geriatric dysphonia prevalence have been limited to ambulatory outpatient and senior communities. Our goal was to identify prevalence of dysphonia in nursing home residents and assisted living residents and search for correlations between indices of dysphonia and indices of frailty. Study Design Prospective epidemiological survey. Methods Residents of a vertically integrated senior care organization who were 65 or older and able to understand and complete the questionnaire wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 15 publications
0
5
0
2
Order By: Relevance
“…Assisted living is frequently said to cater to frail older adults, but few studies report on the proportion of assisted living residents who are frail (Freiheit et al, 2011 ;Hogan et al, 2012 ;Kanwar et al, 2013 ;Nichols, Varadarajan, Bock, & Blumin, 2015 ). In those that do, frailty is common however defi ned (Kanwar et al, 2013 ), but in comparison, frailty is generally felt to be more common and/or severe in long-term care homes (Nichols et al, 2015 ). Different approaches for detecting frailty among assisted living residents may lead to differing prevalence estimates.…”
Section: Assisted Livingmentioning
confidence: 99%
See 1 more Smart Citation
“…Assisted living is frequently said to cater to frail older adults, but few studies report on the proportion of assisted living residents who are frail (Freiheit et al, 2011 ;Hogan et al, 2012 ;Kanwar et al, 2013 ;Nichols, Varadarajan, Bock, & Blumin, 2015 ). In those that do, frailty is common however defi ned (Kanwar et al, 2013 ), but in comparison, frailty is generally felt to be more common and/or severe in long-term care homes (Nichols et al, 2015 ). Different approaches for detecting frailty among assisted living residents may lead to differing prevalence estimates.…”
Section: Assisted Livingmentioning
confidence: 99%
“…It is unclear whether identifying the frailest among assisted living residents substantially helps pick out those at higher risk for adverse outcomes or can be used to direct their care. Predictive models improve only modestly in their ability to anticipate adverse outcomes like mortality, hospitalization, and moving to a higher level of care when frailty is added to characteristics such as age, sex, and co-morbidity (Hogan et al, 2012; Nichols et al, 2015). All residents in assisted living would benefit from a number of the approaches advocated for frail individuals such as advance care planning, encouraging physical activity, and careful stewardship of medications.…”
Section: Screening For Frailty Within the Sectors Of The Canadian Heamentioning
confidence: 99%
“…Uma pesquisa realizada com idosos ativos descreveu prevalência de desvantagem vocal de 9,7% (10) . Outra pesquisa desenvolvida com idosos de uma instituição de longa permanência nos Estados Unidos encontrou prevalência de desvantagem vocal superior (29%) a do presente estudo (24,8%) (27) . Sabe-se que idosos ativos a ser mais funcionais (24) .…”
Section: Resultsunclassified
“…One study indicated that voice-related handicaps differ between robust and frail older adults, particularly on the exhaustion and weight loss domains of the Fried frailty criteria [22], whereas another study suggested a low correlation between voice dysfunction and frailty in nursinghome and assisted-living residents [23]. Given the mixed or scarce evidence, the current study aimed to determine the relationship between frailty and acoustic parameters among older adults.…”
Section: Introductionmentioning
confidence: 94%